The SISAL webApp: exploring the speleothem climate and environmental archives of the world. - Hatvani, István Gábor; Kern, Zoltán; Tanos, Péter; Wilhelm, Micah; Lechleitner, Franziska A.; Kaushal, Nikita (Quaternary Research, 2024)
We present the 'SISAL webApp'—a web-based tool to query the Speleothem Isotope Synthesis and AnaLysis (SISAL) database. The software provides an easy-to-use front-end interface to mine data from the SISAL database while providing the SQL code alongside as a learning tool. It allows for simple and increasingly complex querying of the SISAL database based on various data and metadata fields. The SISAL webApp version currently hosts SISALv2 of the database with 691 records from 294 sites, 512 of which have standardized chronologies. The SISAL webApp has sufficient flexibility to host future versions of the SISAL database, which may include allied speleothem information such as trace elements and cave-monitoring records. The SISAL webApp will increase accessibility to the SISAL database while also functioning as a learning tool for more advanced ways of querying paleoclimate databases. The SISAL webApp is available at http://geochem.hu/SISAL_webApp.